USE OF FOREIGN EXPERIENCE IN INCREASING THE INVESTMENT ATTRACTIVENESS OF REGIONS - A, Akromov A; D.I., Ruziyeva (Antis Publisher, 2024)
General Background: The investment attractiveness of regions plays a crucial role in fostering economic growth, particularly through the lens of foreign direct investment (FDI). Specific Background: This article examines successful international strategies implemented in countries such as Singapore, Poland, Germany, and China, which have effectively increased their FDI through measures like tax incentives, the establishment of free economic zones, and streamlined administrative procedures. Knowledge Gap: Despite the recognized importance of these strategies, there is a lack of comprehensive analysis on how adapting these foreign experiences can be effectively tailored to local contexts, particularly in emerging economies. Aims: This study aims to investigate the applicability of international best practices to enhance Uzbekistan's investment climate, focusing on reforms enacted since 2016. Results: The analysis reveals that reforms, including the Law on Currency Regulation (2017) and the Law on Free Economic Zones (2020), have significantly bolstered Uzbekistan’s FDI, escalating from 2.1 billion in 2018 to 7.5 billion in 2021, marking an impressive growth of over 250%. Novelty: This research contributes to the existing literature by providing a case study of Uzbekistan as an emerging market adapting international investment strategies to its unique economic landscape. Implications: The findings underscore the importance of customizing foreign investment frameworks to local conditions, suggesting that such adaptations can not only promote sustainable economic development but also enhance the overall investment attractiveness of regions in transition.